(De)coloniality in management education: Exploring limits and possibilities - Filho, Valério Carvalho; Rocha Ipiranga, Ana Sílvia; Faria, Alexandre de Almeida (Education Policy Analysis Archives, 2017)
This research considered the context of the University of International Integration of the Afro-Brazilian Lusophony (Unilab) to challenge the subjection of knowledge in general and, specifically, the refoundation of an epistemological pluriversal space in Public Administration. The guiding question of this research was: to what extent the experience of Unilab contributes to the decolonization of practices and knowledge in administration? The main objective is to understand the relationship between intercultural practices and the decolonization of knowledge in administration in the context of Unilab. The qualitative methodology involved an analysis of historical speeches compiled into a broad documentary base and interviews with various subjects, such as professors, students and academic managers active in Unilab. The analysis of the documentary and the narrative discourses of respondents were synthesized into the following categories: production of non-existences, present pasts and controversial latencies in favor of the expansion of the word in administration as a science. Although the practices regarding teaching, research and extension related to the public administration course of Unilab are considerably based on an epistemological universalist legacy, emerging practices interconnect with long-term decolonial latencies, transforming absences into presences and impossibilities into possibilities.